Effects of tecnological variables and the university degree in the creativity ideational - Sanz de Acedo Lizarraga, María Luisa; Sanz de Acedo Baquedano, María Teresa; Ardaiz Villanueva, Oscar (Anales de Psicología / Annals of Psychology, 2012)
The aim of the present study was to examine the effects of three variables -computer tools, technological objects and university degree- in the generation of creative ideas so much to individual level as group. The research was carried out by a sample of 112 pupils of the Pub- lic University of Navarre (Spain) organized in different experimental and control groups according to the requirements of the raised hypotheses. The intervention consisted of the execution of activities that required the subjects the development of ideas on the following fields: solutions to a problem, utilities of some objects and improvements of other objects. The results revealed that the subjects that worked both with computer tools and with technological objects and that belonged to the degree of Technical Engineering in Computer Science of Management, enunciated major number of ideas in the different activities of intervention that the subjects that worked without computer tools, with conventional objects and that belonged to the degree of Social Work. Finally, some relevant conclusions offer in this study.